Desain Pembelajaran Perkalian dengan Permainan Kartu Bilangan di Kelas II SD - Listriani, Listriani; Nasution, Ahmad Sukari (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to produce lesson plans that are in accordance with the 2013 curriculum anddevelop a Math Learning Design Assisted with Number Cards for Grade II Elementary SchoolMultiplication Materials in everyday life. This type of research is research and development usingthe ADDIE (Analysis-Design-Development Implement-Evaluation) model, but this research is only carried out until the development stage. This research was conducted at SDN 105341 DurianVillage. The data collection instrument used is a questionnaire. The subjects in this study were 4validators. The types of data in this study are qualitative data and quantitative data. The results of the questionnaire validation are in the form of learning designs and learning media. The resulting lesson plans are very feasible to use with a score of 80% with the criteria of